Monarch butterflies (Danaus plexippus L.) use a magnetic compass for navigation - Etheredge, Jason A. (National Academy of Sciences, 1999)
Fall migratory monarch butterflies, tested for their directional responses to magnetic cues under three conditions, amagnetic, normal, and reversed magnetic fields, showed three distinct patterns. In the absence of a magnetic field, monarchs lacked directionality as a group. In the normal magnetic field, monarchs oriented to the southwest with a group pattern typical for migrants. When the horizontal component of the magnetic field was reversed, the butterflies oriented to the northeast. In contrast, nonmigratory monarchs lacked directionality in the normal magnetic field. The results are a direct demonstration of magnetic compass orientation in migratory insects.